EXTH-52. USE OF A PHOSPHOLIPID BINDING MARCKS MIMETIC FOR TARGETED KILLING OF GLIOBLASTOMA CELLS. (5th November 2018) - Eustace, Nicholas; Warram, Jason; Widden, Hayley; Anderson, Joshua; Hicks, Patricia; Troelsgaard, Rune; Placzek, William; Hjelmeland, Anita; Gillespie, Yancey; Willey, Christopher
Abstract: Glioblastoma (GBM) like most cancers harbors frequent mutations in phospholipid signaling that contributes to many of the hallmarks of cancer, including immune suppression from the externalization of phosphatidylserine (PS) in viable cells, to pro-growth, survival and invasive signaling resulting from mutations in phosphoinositide (PI) metabolizing enzymes like phosphoinositide 3-kinase p110α (PIK3CA). We evaluated the therapeutic potential of using a PS and phosphatidylinositol 4, 5-bisphosphate (PIP2) binding peptide derived from Myristoylated Alanine-Rich C-Kinase Substrate (MARCKS) effector domain (ED) to suppress GBM growth. The conjugation of a cell penetrating trans-activator of transcription (TAT) sequence to MARCKS ED (TAT-ED) was found to have potent dose-dependent cytotoxicity to GBM patient-derived xenografts (PDX) at low micromolar doses, 20 times greater than the unconjugated ED peptide while remaining nontoxic to normal human astrocytes. A Cy7 labeled TAT-ED showed substantial punctate accumulations at the plasma membrane of GBM but only rarely on NHA's. Quantification of the TAT-ED uptake using the Xcyto10 image cytometer showed TAT-ED accumulates to greater levels in the cytoplasm and nucleus of GBM, poorly penetrates into the nucleus of NHA's, and revealed high levels of TAT-ED was associated with DNA hypoploidy. TAT-ED was equally cytotoxic to PDX neurospheres and adherent cells and found to trigger a rapid and sustained rise in intracellular calcium, with the appearance of a unique annexin V positive bleb, preceding a caspase-independent cell death and simultaneous annexin V positivity and membrane permeability. In vivo bio distribution studies revealed TAT-ED crosses the blood-brain barrier concentrating in the periventricular region of tumor naive mice or in intracranial tumors. Kinomic and mRNA pathway analysis suggests TAT-ED activates PKC, NRD2 and MAPK pathway, while inhibiting ephrin receptors and SRC family kinases. Overall, this study finds TAT-ED to have both selective and potent therapeutic effects against GBM.